Using Credit Subsidies to Counteract a Credit Bust : Evidence From Serbia - Podpiera, Jiri (IMF Working Papers; Working Paper, 2011)
Emerging markets are particularly vulnerable to boom-bust credit cycles, due to excessive capital flows, shallow equity markets, and companies' high leverage and open FX positions. While the policy debate on how to respond to boom-bust credit cycles remains unsettled, it has been conjectured that credit subsidies may provide a particularly effective policy tool to counter a credit bust. This paper reports on a rare policy experiment where credit subsidies were used to buffer the impact of the global financial crisis on Serbia in 2009. Model simulations suggest that credit subsidies in Serbia helped to mitigate the slump in output.